2018
DOI: 10.1002/art.40442
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Sepsis‐Like Features of Neutrophils by Interleukin‐1 Blockade in Patients With Systemic‐Onset Juvenile Idiopathic Arthritis

Abstract: These results strongly support the notion that neutrophils play an important role in systemic-onset JIA, especially in the early inflammatory phase of the disease. The findings also demonstrate that neutrophil numbers and the inflammatory activity of systemic-onset JIA are both susceptible to IL-1 blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 52 publications
4
44
0
1
Order By: Relevance
“…Our single‐center, prospective cohort study may provide a first step toward personalized medicine for systemic JIA. The predictive value of neutrophil counts for response to rIL‐1Ra supports findings from a previous study of our cohort, which provided evidence that neutrophils have an important role in the early inflammatory phase of systemic JIA . Our findings suggest that, especially in the early phase of systemic JIA, which is characterized by pronounced innate immune activation and neutrophilia, patients may be highly responsive to IL‐1 blockade, indicating the existence of a window of opportunity.…”
Section: Discussionsupporting
confidence: 88%
“…Our single‐center, prospective cohort study may provide a first step toward personalized medicine for systemic JIA. The predictive value of neutrophil counts for response to rIL‐1Ra supports findings from a previous study of our cohort, which provided evidence that neutrophils have an important role in the early inflammatory phase of systemic JIA . Our findings suggest that, especially in the early phase of systemic JIA, which is characterized by pronounced innate immune activation and neutrophilia, patients may be highly responsive to IL‐1 blockade, indicating the existence of a window of opportunity.…”
Section: Discussionsupporting
confidence: 88%
“…In human experimental endotoxemia, peripheral neutrophils exhibit a functional heterogeneity and different degrees of priming ( 122 ). Similar variations in neutrophil phenotypes are seen in the peripheral blood of patients during severe inflammation ( 137 ). A large number of immature or banded cells, suppressive neutrophils, myeloid-derived suppressor cells, and neutrophil progenitor cells can be detected ( 119 ).…”
Section: The Importance Of Neutrophils In Inflammatory Complications supporting
confidence: 58%
“…Ter Haar et al showed that neutrophils played an important role in the early inflammatory phase of sJIA, and the number and inflammatory activity of neutrophils were highly sensitive to the blockade of IL-1 signaling [ 105 ]. To examine activated neutrophil subsets, Brown et al isolated neutrophils from children with active sJIA or clinically inactive disease (CID) [ 106 ].…”
Section: Transcriptome Study Of Jiamentioning
confidence: 99%